Spontaneous remission of nephrotic syndrome associated with COVID-19 infection in an 8-year-old boy - Akyol, Aylin Kayalı; Dinç, Gamze Akça; Mustafaoğlu, Özlem; Yahşi, Aysun; Bayhan, Gülsüm İclal and Özlü, Sare Gülfem (The Turkish Journal of Pediatrics, 2022)
Background. It is already known that viral infections, exclusively upper respiratory tract infections may trigger relapses of nephrotic syndrome. Recently, COVID-19 disease has also been reported to be related with relapse of nephrotic syndrome in a few pediatric cases Case. Here we present an 8-year-old boy who had relapse of nephrotic syndrome due to COVID-19 infection. He was asymptomatic except for mild edema. He was managed supportively, no medication was started and went into spontaneous remission in 7 days. Conclusions. Viral infections particularly upper respiratory tract infections may trigger relapse of nephrotic syndrome. COVID-19 has also been reported to be related with relapses of nephrotic syndrome in a few pediatric cases. Spontaneous remission in our patient indicates the importance of close monitoring of patients before starting long term treatment with steroids.